P1059REMOVAL OF LOW MOLECULAR WEIGHT AND PROTEIN-BOUND UREMIC RETENTION SOLUTES WITH ALLO-HEMODIALYSIS: RESULTS FROM EX VIVO STUDY. (6th June 2020) - Maheshwari, Vaibhav; Grobe, Nadja; Chao, Joshua; Tao, Xia; Thijssen, Stephan; Kotanko, Peter
Abstract: Background and Aims: It is projected that in 2030, 14.5 million people will have end stage kidney disease and need kidney replacement therapy, yet only 5.4 million will receive it due to economic, social, and political factors. We have proposed allo-hemodialysis (alloHD) as a simple and low-cost HD alternative (https://www.kidneynews.org/kidney-news/features/buddy-dialysis-probed-hemodialysis-alternative ). In alloHD, the patient's blood is dialyzed against the blood of a healthy subject ('buddy'), who receives the excess fluid and uremic solutes and excretes them via his/her healthy kidneys. Method: We conducted ex vivo experiment with bovine whole blood, 4L in a patient and buddy bucket, respectively. In this setup, buddy blood flows through the dialyzer fiber lumen, while patient blood flows in the dialysate space (Nipro Cellentia 17H dialyzer). The patient blood was spiked with urea, creatinine, potassium chloride, indoxyl sulfate (IS), and p-cresyl sulfate (pCS); solute levels on the buddy side were not altered. The alloHD session lasted for 3 hours, the ultrafiltration (UF) volume was 750 mL. The blood flow rates were kept constant at 150 and 200 mL/min on the patient and buddy side, respectively. Heparin (5000 IU/L) was added to either bucket. The alloHD machine prototype comprises 2 pumps on the buddy side and one on patient side (Figure 1A ). UF is controlled by the blood flow rate differential between the buddy-sided arterial and venous pumps, respectively. Results: The levels of small unbound solutes (urea, creatinine, potassium) equilibrate quickly between patient and buddy buckets (Fig. 1B, top panel ). Of note, the buddy-sided potassium equilibrium concentration is lower, because ongoing UF dilutes albumin in the buddy bucket and concentrates it in the patient bucket, resulting in a Gibbs-Donnan potential. The protein-bound uremic solutes IS and pCS equilibrate towards lower total concentrations on the buddy side due to the earlier mentioned UF-induced albumin dilution. Of note, the levels of free IS and pCS, respectively, converge on both sides of the dialyzer membrane (Fig 1B, bottom panel ). Conclusion: Our ex vivo data suggest that alloHD can be used to treat hyperkalemia, a major cause of death in acute and chronic kidney failure. Both unbound and protein-bound low molecular weight uremic solutes are also removed. With elimination of "classical" dialysate, we simplify the HD procedure and reduce machine size and costs significantly, making it an affordable HD alternative. Feasibility and efficacy studies in animal models are the next step.